1996
DOI: 10.1097/00004728-199601000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of the Ligamentum Arteriosum in Adults: CT Features

Abstract: On unenhanced chest CT calcification of the ligamentum arteriosum is a common finding in adults and increases in prevalence with increasing age and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 4 publications
1
15
1
Order By: Relevance
“…Since LAC was present in one patient at 10 years of age but was absent 3 years later, they suggested that LAC usually develops within the first 7 years of life but disappears within a few years. Another study reported that the prevalence of LAC on unenhanced chest CT in adults was 48 %, much higher than the 11.2 % we observed, and that the prevalence was higher in adults with atherosclerotic calcification (65 %) than in adults without other calcifications (21 %) [6]. This discrepancy may be due to the difference in CT scan technique.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Since LAC was present in one patient at 10 years of age but was absent 3 years later, they suggested that LAC usually develops within the first 7 years of life but disappears within a few years. Another study reported that the prevalence of LAC on unenhanced chest CT in adults was 48 %, much higher than the 11.2 % we observed, and that the prevalence was higher in adults with atherosclerotic calcification (65 %) than in adults without other calcifications (21 %) [6]. This discrepancy may be due to the difference in CT scan technique.…”
Section: Discussioncontrasting
confidence: 76%
“…In contrast, conventional CT showed that the prevalence of LAC was higher in adults (48 %, 194/402) than in children (13 %, 7/53) [6,7]. On multi-section CT, however, LAC seems to be detected more frequently than conventional CT.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…11,12 Potential links between calcification and atherosclerosis have recently been proposed. 13 Whereas natural or synthetic calcification can be detected by x-ray diffraction (CT), 14 B-mode echography, 15 or MRI, 16 quantification of calcium salts in biological samples still requires that the tissue sample be delipidated and then digested with concentrated acid before standard chemical assays are performed. 17,18 Therefore, introduction of simple and reliable instrumental methods to quantify the plaque composition (ex vivo) will be useful for the interpretation and calibration of the in vivo measurements.…”
mentioning
confidence: 99%
“…Calcification of the ligamentum arteriosum and/or of the aortic wall in the aortic isthmus area. This calcification in the adults may be in several patterns such as curvilinear, punctate or clumped, and in incidence up to 65% [8]. In our case, we chose the surgical instead of the endovascular-intervention, for the following two reasons.…”
Section: Discussionmentioning
confidence: 99%